Promoting Student Autonomy Through Self-Assessment and Learning Strategies (2003)
ABSTRACT: In this article, a teacher-researcher and her advisor report on an action-research project aimed at developing student autonomy through the implementation of self-assessment and learning strategies, in an English course for students of different academic programs in a well-known university in Medellín. Affective factors, metacognition, the role of the teacher and linguistic achievement emerged as the main themes related to developing learner autonomy. In this paper the authors aim at a better understanding and discussion on how motivation affects students' decisions regarding planning, monitoring and evaluating their learning, and how this regulation process and the facilitating role of the teacher helps them broaden their learning strategies and improve their linguistic performance.